Polyphenolic Composition of Quercus suber Cork from Different Spanish Provenances - Conde, Elvira; Cadahía, Estrella; García-Vallejo, María Concepción; Fernández de Simón, Brígida (Journal of Agricultural and Food Chemistry, 1998)
Polyphenolic composition was studied by HPLC and classical chemical methods in reproduction cork of Quercus suber from different Spanish provenances. The low molecular weight polyphenols (gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferyl, and sinapic aldehydes; and aesculetin and scopoletin) and the ellagitannins (roburins A and E, grandinin, vescalagin, and castalagin) were identified and quantified. Ellagic acid was the main component in the ether soluble fraction, and the group of hydrolyzable tannins, and among them castalagin, was the most abundant in the tannic extract in all the samples. Although there was an important variability among provenances, no significant differences were found in the total tannin content and in the individual content of each ellagitannin. However, gallic and caffeic acids and protocatechuic aldehyde provided the greatest discrimination among provenances. Keywords: Quercus suber; cork; polyphenols; tannins; phenolic acids and aldehydes; coumarins; ellagitannins; high-performance liquid chromatography
doi: 10.1021/jf970863k
Keywords: Cork; coumarins; ellagitannins; high-performance liquid chromatography; phenolic acids and aldehydes; polyphenols; Quercus suber; Tannins

Polyphenolic Composition of Quercus suber Cork from Different Spanish Provenances - Conde, Elvira; Cadahía, Estrella; García-Vallejo, María Concepción; Fernández de Simón, Brígida (Journal of Agricultural and Food Chemistry, 1998)
Polyphenolic composition was studied by HPLC and classical chemical methods in reproduction cork of Quercus suber from different Spanish provenances. The low molecular weight polyphenols (gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferyl, and sinapic aldehydes; and aesculetin and scopoletin) and the ellagitannins (roburins A and E, grandinin, vescalagin, and castalagin) were identified and quantified. Ellagic acid was the main component in the ether soluble fraction, and the group of hydrolyzable tannins, and among them castalagin, was the most abundant in the tannic extract in all the samples. Although there was an important variability among provenances, no significant differences were found in the total tannin content and in the individual content of each ellagitannin. However, gallic and caffeic acids and protocatechuic aldehyde provided the greatest discrimination among provenances. Keywords: Quercus suber; cork; polyphenols; tannins; phenolic acids and aldehydes; coumarins; ellagitannins; high-performance liquid chromatography
doi: 10.1021/jf970863kdoi: 10.1021/jf970863kThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; coumarins; ellagitannins; high-performance liquid chromatography; phenolic acids and aldehydes; polyphenols; Quercus suber; Tannins

Low Molecular Weight Polyphenols in Cork of Quercus suber - Conde, Elvira; Cadahía, Estrella; García-Vallejo, María Concepción; Fernández de Simón, Brígida; González Adrados, José Ramón (Journal of Agricultural and Food Chemistry, 1997)
Low molecular weight polyphenols were studied by HPLC in samples of cork from different trees of Spanish Quercus suber and at different industrial processing stages. Gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferylic, and sinapic aldehydes, and aesculetin and scopoletin were identified and quantified. Ellagic acid was the main component in all of the samples, followed by the rest of the phenolic acids, which had very much lower concentrations. Four components, caffeic, ferulic, and protocatechuic acids and vanillin, were selected as those that provided the greatest differences among the trees studied. In relation to the four industrial processing stages considered, marked differences were observed between the first two stages, stripping and first rest, and the stages after boiling. In this case, the discriminant variables were coniferaldehyde, sinapaldehyde, and ellagic acid. Keywords: Quercus suber; cork; polyphenols; phenolic acids and aldehydes; coumarins; high-performance liquid chromatography
doi: 10.1021/jf960486wdoi: 10.1021/jf960486wThe following values have no corresponding Zotero field: publisher: American Chemical Society
Keywords: Cork; coumarins; high- performance liquid chromatography; phenolic acids and aldehydes; polyphenols; Quercus suber

Low Molecular Weight Polyphenols in Cork of Quercus suber - Conde, Elvira; Cadahía, Estrella; García-Vallejo, María Concepción; Fernández de Simón, Brígida; González Adrados, José Ramón (Journal of Agricultural and Food Chemistry, 1997)
Low molecular weight polyphenols were studied by HPLC in samples of cork from different trees of Spanish Quercus suber and at different industrial processing stages. Gallic, protocatechuic, vanillic, caffeic, ferulic, and ellagic acids; protocatechuic, vanillic, coniferylic, and sinapic aldehydes, and aesculetin and scopoletin were identified and quantified. Ellagic acid was the main component in all of the samples, followed by the rest of the phenolic acids, which had very much lower concentrations. Four components, caffeic, ferulic, and protocatechuic acids and vanillin, were selected as those that provided the greatest differences among the trees studied. In relation to the four industrial processing stages considered, marked differences were observed between the first two stages, stripping and first rest, and the stages after boiling. In this case, the discriminant variables were coniferaldehyde, sinapaldehyde, and ellagic acid. Keywords: Quercus suber; cork; polyphenols; phenolic acids and aldehydes; coumarins; high-performance liquid chromatography
doi: 10.1021/jf960486w
Keywords: Cork; coumarins; high- performance liquid chromatography; phenolic acids and aldehydes; polyphenols; Quercus suber